Analisis Pengaruh Biaya Pendidikan Terhadap Peningkatan Aset Dan Laba Pada Perbankan Syariah Di Indonesia - Ridwansyah (Jurnal Ekonomi, 2017)
One of the keys to maintaining the quality of Syariah pious performance of BUS or UUS and BPRS is to develop and educate employees to maintain superior quality of human resources as well as be ready and able to become the locomotive of Syariah banking development in Indonesia. Training and development activities provide dividends to employees and companies, in the form of skills and skills that will further be a valuable asset for the company. This study aims to determine how much influence the cost of education to increase the number of assets and profits derived by Islamic banking in Indonesia both BUS, UUS and BPRS. The method used in this research is a quantitative method by using secondary data in the form of a report of educational cost level and increasing amount of assets and profit in BUS or UUS and BPRS in Indonesia during the 2009-2013 period. For the data analysis process, this research uses simple linear regression analysis and hypothesis t-test with educational cost in BUS or UUS and SRB as the independent variable (X) and total assets and profit in BUS or UUS and BPRS as dependent variable (Y). Looking at the results of statistical tests using SPSS tools can be seen that the cost of education does not affect the amount and amount of assets and profits owned by BUS or UUS and BPRS in Indonesia.